The Influence of Implementing an Online Registration System Through the Application On Reducing Queues at The Bandung Muhammadiyah Hospital - Nur Azizah, Faridah; Susi Susanti, Ai (Asian Journal of Environmental Research, 2024)
This research is a qualitative study with a phenomenological approach using interview and survey data collection techniques that aim to gain an in-depth understanding of the patient experience in online hospital registration. The research participants included staff, patients, and patients' families who used the online registration system at Muhammadiyah Bandung Hospital. The results of this study show that patients' experiences with the online registration system include phenomenological aspects. Patients described changes to registration, including ease of access, flexibility of scheduling, and ease of registration through the application or hospital website. It was stated that patients could register online at any time if they wanted to visit. In addition, some patients experienced difficulties in using the online registration system. For example, the clinic you want to visit has a limited quota, the doctor's schedule is not updated, or other obstacles. The use of an online registration system also has benefits in reducing queues at the hospital. Patients said they could avoid long queues and shorten waiting times by registering themselves online. The study concluded that patients' experiences with online registration involved changes in access, control, and waiting time. Although there were some challenges, patients found solutions and benefits in the online registration system. This study highlights the importance of continuously improving technical, interface, and user experience improvements to provide patients with a better experience when using the online registration system.